From reactor to rheology in industrial polymers. Issue 2 (16th July 2014) - Read, Daniel J.
ABSTRACT This article reviews current efforts towards quantitative prediction of rheological properties of industrial polymer resins, based upon their polydisperse branched molecular structure. This involves both an understanding of how reactor and reaction conditions influence the distribution of chain lengths and branch placement (which is the province of reactor engineering) and an understanding of how the molecular structures in turn give rise to the rheology (the province of polymer physics). Both fields are reviewed at an introductory level, focussing in particular on developments in theoretical prediction of rheology for both entangled model polymers and industrial polymers. Finally, we discuss three classes of reaction for which the fields of reactor engineering and polymer physics have been truly combined to produce predictions from reactor to rheology. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 123–141